PELESTARIAN RITUAL NYALAMAQ DILAUQ SEBAGAI FESTIVAL PARIWISATA MASYARAKAT PESISIR DI DESA WISATA TANJUNG LUAR KABUPATEN LOMBOK TIMUR - Baiq Niki Cikita Dwi Daya; I Made Suyasa; Ajuar Abdullah (Program Studi S1 Pariwisata, Sekolah Tinggi Pariwisata Mataram, 2023)
Tanjung Luar Village is one of the villages in Keruak District, East Lombok Regency. This village is a coastal area so most of the population works as fishermen, therefore their lives are very dependent on the sea. So the people of Tanjung Luar village really care for and protect the sea, conducting a sea rescue ceremony or what is called Nyalamaq Dilauq. The purpose of this study was to determine the procession of the implementation of the Nyalamaq Dilauq ritual in the village of Tanjung Luar, and to determine the form of preserving the Nyalamaq Dilauq ritual as a tourism festival for coastal communities in the village of Tanjung Lua. The method used in this research is descriptive qualitative using data collection techniques in the form of observation, interviews, Focus Group Discussio), and documentation. Meanwhile, to analyze the data, the researcher used descriptive qualitative analysis. The results of this study indicate that in the procession of carrying out the Nyalamaq Dilauq ritual as a tourism festival in the village of Tanjung Luar, includes the determination of the day of implementation, the meaning of symbols in the Nyalamaq Dilauq ceremony and the need for ritual implementation, the stages of implementing the Nyalamaq Dilauq ritual, the end the Nyalamaq Dilauq ritual and the form of preservation of the Nyalamaq Dilauq ritual as a tourism festival for coastal communities in Tanjung Luar village, East Lombok Regency.